Rationale and Design of the Effectiveness of LowEr maintenanCe dose of TicagRelor early After myocardial infarction (ELECTRA) pilot study. Issue 3 (8th November 2017) - Kubica, Jacek; Adamski, Piotr; Buszko, Katarzyna; Kubica, Aldona; Kuliczkowski, Wiktor; Fabiszak, Tomasz; Jilma, Bernd; Alexopoulos, Dimitrios; Paciorek, Przemysław; Navarese, Eliano P
Abstract: Aims: The degree and time course of platelet inhibition using ticagrelor can vary during the acute phase and the following stable period after acute myocardial infarction (AMI). The optimal level of platelet inhibition during the various stages of AMI remains an open question. The aim of the current study is to compare the antiplatelet efficacy of two ticagrelor maintenance dose regimens (60 mg b.i.d. vs. 90 mg b.i.d.) in stable patients following an initial strategy with ticagrelor 90 mg b.i.d. during the first month after AMI. Methods and results: The Effectiveness of LowEr maintenanCe dose of TicagRelor early After myocardial infarction (ELECTRA) pilot study is a phase III, single-centre, randomized, open-label, pharmacokinetic/pharmacodynamic trial. The study population will include 50 patients with AMI treated with percutaneous coronary intervention. At Day 30 post-AMI, all trial participants will be randomly assigned in 1:1 ratio to receive either reduced (60 mg b.i.d.) or standard (90 mg b.i.d.) maintenance ticagrelor dose until Day 45 post-AMI. Platelet function testing in each patient will be performed using up to two different methods (the VASP assay and multiple electrode aggregometry). Pharmacokinetics of ticagrelor and its active metabolite (AR-C124910XX) will be assessed by liquid chromatography mass spectrometry. Conclusion: A de-escalation strategy with reduced dose of ticagrelor (60 mg b.i.d.) following an initial standard dose (90 mg b.i.d.) during the first month after AMI may provide equally effective platelet inhibition as compared to maintenance with the standard ticagrelor dose. ClinicalTrials. gov Identifier: NCT03251859.